Validação da metodologia para análise de saxitoxina e dc-saxitoxina em água via derivatização pré-coluna - Silvino, Larissa Sousa (2014)
The intensification of eutrophication in the watershed is caused by human actions and is the predominant cyanobacteria. In turn, these blooms affecting the quality of the water supply for the population, and, when disrupted, can release toxins (cyanotoxins) causing intoxication. The first in situ confirmation of the death by poisoning of humans with cyanotoxins in Brazil led the WHO to quickly publish new Ordinance on monitoring of raw water quality that incorporate new indicators, as the concentration of the cyanobacteria and their toxins in water sources used for drinking water supply. Thus, technologies for water treatment and for the identification and quantification of cyanotoxins have been going through a process of improvement. In this context, this study aimed to validate the method of reverse phase liquid chromatography with fluorescence detection (HPLC-FLD) and pre-column derivatization for detection and quantification of cyanotoxins saxitoxin (STX) and decarbamoil-saxitoxin (dc-STX) from the cyanobacterium Cylindrospermopsis raciborskii cultivation. This validation was performed to give credibility to the analytical method and the selected parameters were: selectivity, linearity, limit of detection (LOD) and quantification (LOQ), accuracy, precision and robustness. The results showed good selectivity, confirming that the method had the ability to measure the toxins in a Post Extraction matrix in the presence of other components. The analytical curves were constructed with nine points from the patterns of STX and dc-STX. The method showed linearity in the range of 4.5 to 150 mg L-1 for STX and 3.0 to 132 mg L-1 to dc-STX, and the correlation coefficient (r) greater than 0.99 for both toxins, showing that the method has the capacity to deliver results directly proportional to the concentration of analyte detected. The sensitivity was measured by the LD and LQ, obtaining satisfactory for the purposes of work results. The method achieved good precision and accuracy, whereas for STX and dc-STX different concentration levels were with values ​​within the ranges allowed by Brazilian standards for validation, and showed to be robust because it was insensitive to small variations possible to occur during analysis. In summary, one can consider that the method used for the detection and quantification of cyanotoxins STX and dc-STX showed satisfactory results, since the parameters analyzed to validate it were in conformity with the accepted values ​​in Brazilian standards.